Reduction of Gas CO2 to CO with High Selectivity by Ag Nanocube-Based Membrane Cathodes in a Photoelectrochemical System - Lu, Weiwei; Zhang, Yuan; Zhang, Jinjin; Xu, Peng (Industrial & engineering chemistry research, 2020)
Photoelectrochemical (PEC) reduction of CO2 is a potential way to simultaneously address environmental problems and reduce the energy crisis. However, traditional conversion of CO2 in aqueous solution has serious drawbacks, such as low solubility, slow diffusion, and complicated existing form of CO2 in water, as well as the competitive H2 evolution from reduction of H2O, leading to unsatisfactory conversion efficiency and poor product selectivity. To overcome these problems, in this work, gas CO2 has been directly introduced to a flow cell, in which a membrane cathode assembly with Ag nanocube electrocatalysts is used. It is surprising to find that with this PEC reduction strategy, the product selectivity of CO can be substantially enhanced with the suppression of competitive H2 evolution. The control experiments and theoretical calculations suggest that the facile mass transfer of gas CO2 to the (100) plane of Ag nanocubes electrocatalysts and the suitable photocurrent density may account for such advantages.